Energy Policy Goals and Behavioural Change: Insights from Universiti Tun Hussein Onn Malaysia - Ismail, Muhammad Syahmirul; Ishak, Mohd Hafizal; Md Yassin, Azlina; Ahmad, Nurul Afiqah; Masram, Haidaliza; Thanaraju, Puvaneswary a/p (Research in Management of Technology and Business, 2026)
An energy policy is crucial for a university to manage its environmental impact, control costs, and enhance its reputation while promoting sustainability. Previous research shows that the behaviours of students and staff significantly influence energy consumption on campus, making it vital to address these behaviours within the energy policy framework. This study aims to identify the elements of UTHM's energy program and analyse how its goals affect the behaviour of students and staff. A qualitative approach was used, including semi-structured interviews with two energy management experts and a questionnaire survey of 100 respondents from the university. The interviews highlighted the importance of economic efficiency in the energy program, with the top three behaviours being temperature control, energy conservation practices, and prioritising economic efficiency. The primary objective of the energy policy is to achieve economic efficiency while maintaining comfortable living conditions. While the energy program has a significant influence on practices and cognitive norms, its impact on the broader energy culture is less pronounced.